Compare Short Term Post-Operative Complication of Laparoscopic Transabdominal Preperitoneal (TAPP) and Lichtenstein’s Tension Free Hernia Repair - Mashal Nazir, Rahman Ullah, Aqsa Saleema, Nisar Ahmed, Javaid Sajjad Hashmi, Muhammad Tariq Khan, Ibrahim Shujjah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare short term post-operative complication of laparoscopic transabdominal preperitoneal (TAPP) and Lichtenstein’s tension free hernia repair. Study Design: Randomized clinical trial. Place & Duration of Study: Surgical Unit of Khyber Teaching Hospital (KTH) Peshawar during the period of 6 months from 1st January, 2020 to 30 June, 2021. Material and Methods: In this study 492 cases of inguinal Hernia with 246 in each group. For group A, laparoscopic TAPP repair were performed with 10cmx 15cm polyprophlene mesh (prolene-Ethicon) and were fixed with tackers (Protack 5mm fixation device - covidien). For Group B Lichtenstein’s repair were performed through supra inguinal incision, using 10cmx 15 cm polypropylene mesh (prolene- ethicon). Then the patients were monitored for short term post-operation complication post-operatively. Results: Our study shows that in Group A(Laparoscopic TAPP) mean age was 42 years with SD ± 8.13 and in Group (Lichtenstein repair) mean age was 45 years with SD ± 8.13. In Group A (Laparoscopic TAPP) 99% patients were male and 1% patients were female while in Group B (Lichtenstein repair) 99% patients were male and 1% patients were female. In Group A(Laparoscopic TAPP), urinary retention was 5(2%), hematoma was 5(2%), surgical site infection was 10(00%), Ischemic orchitis was 2(1%), seroma was 20(8%) While in Group B (Lichtenstein repair). urinary retention was 25(10%), hematoma was 39(16%), surgical site infection was 66(27%), Ischemic orchitis was 5(2%), seroma was 54(22%). Conclusion: Frequency of short term post operative complication are higher in Lichtenstein’s tension free hernia repair as compare to laparoscopic transabdominal preperitoneal (TAPP) group. Keywords: Short Term, Post-Operative Complication, Laparoscopic Transabdominal Preperitoneal (TAPP), Lichtenstein’s Tension Free, Hernia Repair.